Long‐Term Administration of Eicosapentaenoic Acid Improves Post–Myocardial Infarction Cardiac Remodeling in Mice by Regulating Macrophage Polarization. Issue 2 (21st February 2017) - Takamura, Masayuki; Kurokawa, Keisuke; Ootsuji, Hiroshi; Inoue, Oto; Okada, Hikari; Nomura, Ayano; Kaneko, Shuichi; Usui, Soichiro
Abstract : Background: Consumption of n‐3 fatty acids reduces the incidence of cardiovascular mortality in populations that consume diets rich in fish oil. Eicosapentaenoic acid (EPA) is an n‐3 fatty acid known to reduce the frequency of nonfatal coronary events; however, the frequency of mortality after myocardial infarction (MI) is not reduced. The aims of this study were to determine whether long‐term administration of EPA regulated cardiac remodeling after MI and to elucidate the underlying therapeutic mechanisms of EPA. Methods and Results: C57BL/6J mice were divided into control (phosphate‐buffered saline–treated) and EPA‐treated groups. After 28 days of treatment, the mice were subjected to either sham surgery or MI by left anterior descending coronary artery ligation. Mortality due to MI or heart failure was significantly lower in the EPA‐treated mice than in the phosphate‐buffered saline–treated mice. However, the incidence of cardiac rupture was comparable between the EPA‐treated mice and the phosphate‐buffered saline–treated mice after MI. Echocardiographic tests indicated that EPA treatment attenuated post‐MI cardiac remodeling by preventing issues such as left ventricular systolic dysfunction and left ventricle dilatation 28 days after MI induction. Moreover, during the chronic remodeling phase, ie, 28 days after MI, flow cytometry demonstrated that EPA treatment significantly inhibited polarization toward proinflammatory M1 macrophages, but not anti‐inflammatory M2 macrophages, in the infarcted heart. Furthermore, EPA treatment attenuated fibrosis in the noninfarcted remote areas during the chronic phase. Conclusions: Long‐term administration of EPA improved the prognosis of and attenuated chronic cardiac remodeling after MI by modulating the activation of proinflammatory M1 macrophages.